The Engineering Properties Of High Strength A Dynamic Agent-Based Model For Simulating And Predicting Urban Growth - Mahamud, Mohd Amirul (2021)
Rapid urbanisation has become a significant phenomenon that concerns all nations as the world shifted into a globalisation era. While developed countries have faced this rapid urbanisation since the late 19th centuries, developing countries are struggling to manage this phenomenon after the 1950s. Understanding the urban growth system is the first step towards achieving future sustainable urbanisation. Spatially dynamic urban growth models can provide valuable simulations that contain essential knowledge in planning and policy-making. Most developed urban growth models implemented a uniform rate of urban growth to predict potential future urban growth outcomes, which is different from the real world. Thus, this thesis aims to develop an agent-based urban growth model that allows non-uniformity in urban growth rate.